Measurement and Determinants of UPNM Internal Research Grant Performance - SALLEH, MOHD SHARIL; Dollah, Noor Azman; Ahmad, Kol Prof. Dr. Khairol Amali (Research in Management of Technology and Business, 2024)
The Short Term Research Grant is a competitive grant and fully funded by the University Pertahanan Nasional Malaysia. This article describes a best practice implementation in research management by the Division of Research and Innovation to a grant batch between the year 2014 and 2024. Although there has been significant investment starting from the year 2014, research publications trend in high-impact journals such as Web of Science, SCOPUS and Indexed Journal are still under par. Data finding consistently shows that most publications are only submitted and accepted in the second year of the grant being awarded. This study evaluates the relationship between the number of publications and total projects funded to the UPNM Internal Research Grant. By employing correlation analysis, a significant positive relationship was identified, with a correlation coefficient of 0.92, indicating that an increase in the number of projects typically leads to a corresponding rise in publications. The relationship is further quantified through a linear model using SPSS, showing that each additional project contributes approximately 0.91 publications. The model’s negative intercept suggests an adjustment for baseline publication rates, indicating a threshold of project activity necessary to generate measurable publication output. This analysis underscores the critical role of project volume in driving research productivity and highlights the importance of optimising resource allocation to enhance both the quantity and quality of research outputs. Therefore, the study offers useful information concerning management of research and more specifically utilisation of research funds in universities. Moreover, this data could provide a solid basis for the Division of Research and Innovation, Universiti Pertahanan Nasional Malaysia to refine its research grant management strategy, aiming to enhance its performance in the Malaysia Research Assessment (MyRA) rating.